In vitro concentration optimization of ethanol extract from Makasar fruit seeds (Brucea javanica L. Merr) as an anti-inflammatory agent - Diva Almira; Windah Anugrah Subaidah; Agus Dwi Ananto; Rizqa Fersiyana Deccati; Handa Muliasari (Jurnal Pijar Mipa, 2021)
Anti-inflammatory medications are necessary to treat excessive inflammation reactions due to injury, infection, or irritation. The emergence of several adverse effects associated with synthetic anti-inflammatory drugs has prompted the continued use of anti-inflammatory agents derived from natural products with low side effects and a high therapeutic effect. While it is well established that the seeds of the Makassar fruit (Brucea javanica (L.) Merr.) ÃÂ have anti-inflammatory activity, the optimal concentration of Makasar fruit seed extract for anti-inflammatory activity is unknown. This study aims to determine the optimal Makassar fruit seed extract concentration as an in vitro anti-inflammatory. The seeds of the Makasar fruit were extracted using the sonication method (3 x 35 minutes) in 96% ethanol and then concentrated using a rotary evaporator. The secondary metabolites of Makasar fruit seed extract were then identified in the test tubes, and the anti-inflammatory activity was determined using the protein denaturation inhibition method. The results indicated that the extract produced had a yield of 10.03%. The Makassar fruit seed extract contains secondary metabolites of phenolics, flavonoids, and terpenoids. Makasar fruit seed extract exhibited the optimum anti-inflammatory activity at a concentration of 1%, with a 55.47%ÃÂ inhibition of protein denaturation.